Konvolutionäre neuronale Netze in der industriellen Bildverarbeitung und Robotik - Mitschke, Norbert (Forschungsberichte aus der Industriellen Informationstechnik, 2022)
In the first part of this dissertation, a framework for the design of a CNN for FPGAs is presented, consisting of a preprocessing algorithm, an augmentation technique, a custom quantization scheme and a pruning step of the CNN. The combination of conventional image processing with neural networks is shown in the second part by an example from robotics, where an image-based visual servoing process is successfully conducted for a gripping process of a robot.